Catalyzing Growth: The Interplay of Governance and Market Development in Achieving SDGs - Fadila, Ardhiani; Pangestuti, Dewi Cahyani (Nominal: Barometer Riset Akuntansi dan Manajemen, 2025)
Stock market development is influenced by various factors, including governance quality. This study analyzes the impact of the World Governance Indicators (WGI) on stock market development in Indonesia from 2008 to 2022 using regression analysis and non-parametric robustness tests. The WGI indicators examined include Voice and Accountability, Political Stability, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption. The regression analysis results indicate that none of these indicators significantly affect stock market capitalization. However, the robustness test using Spearman correlation with quartile-based categorization reveals that Rule of Law and Voice & Accountability significantly correlate with stock market capitalization, highlighting the importance of institutional quality in investor confidence. Additionally, inflation negatively impacts market capitalization, while GDP growth does not exhibit a significant effect. The findings suggest that strengthening legal frameworks and enhancing government transparency are crucial for fostering a stable and attractive investment climate. Keywords: World Governance Indicators, Capital Market, Inflation, GDP ABSTRAK Perkembangan pasar modal dipengaruhi oleh berbagai faktor, termasuk kualitas tata kelola. Penelitian ini menganalisis pengaruh World Governance Indicators (WGI) terhadap perkembangan pasar modal di Indonesia selama periode 2008-2022 dengan menggunakan analisis regresi serta pengujian robustnes non-parametrik. Indikator WGI yang diteliti mencakup Voice and Accountability, Political Stability, Government Effectiveness, Regulatory Quality, Rule of Law, dan Control of Corruption. Hasil regresi menunjukkan bahwa tidak ada indikator ini yang secara signifikan mempengaruhi kapitalisasi pasar. Namun, uji robustnes menggunakan korelasi Spearman dengan kategorisasi kuartil mengungkapkan bahwa Rule of Law dan Voice & Accountability memiliki korelasi signifikan dengan kapitalisasi pasar, menegaskan pentingnya kualitas institusi dalam meningkatkan kepercayaan investor. Selain itu, inflasi memiliki dampak negatif terhadap kapitalisasi pasar, sedangkan pertumbuhan PDB tidak menunjukkan pengaruh signifikan. Temuan ini menekankan bahwa penguatan kerangka hukum dan peningkatan transparansi pemerintahan sangat penting untuk menciptakan iklim investasi yang stabil dan menarik. Kata Kunci: World Governance Indicators, Pasar Modal, Inflasi, PDB